Defining Russia Musically: Historical and Hermeneutical Essays - Taruskin, Richard (Princeton, NJ Princeton University Press, 2000)
A passionate vision of what Russian music has meant both as an expression and as a shaping force of the country's character. . . . [Taruskin is] an exceptionally gifted critic. . . . [T]he connections between technique and expression are formidably argued, and it is the capacity to do this, with patience and depth of understanding and with a vast knowledge of the literature, that gives Taruskin's criticism its quality. -- John Warrack, Time Literary SupplementTaruskin's work is far too rich and multi-layered, steeped in Russian intellectual history, literature, and culture, even to synopsize in a short review. . . . His newest book is essential for musicologists wishing to understand Russia's place in music, and for Slavists wishing to understand music's place in Russia. -- Robert W. Oldani, The Russian ReviewMore than a musicologist, Richard Taruskin is a cultural critic who deserves non-scholarly readers. His brilliant and alarmingly timely book Defining Russia Musically is about the battle for a nation's soul--fought between Europe and Asia, modernity and primitivism--in the music of Tchaikovsky and Shostakovich. -- Peter Conrad, The ObserverTaruskin's hallmarks are evident throughout: research of almost astonishing breadth, impatience with facile views and those who propound them, and contempt for formalist modes of analysis that ignore the extramusical. This is an important, challenging book; no other book in English covers this ground with equal depth or brilliance. -- "ChoiceWhen this controversial book first appeared in hardback, it sparked a debate . . . both because of and despite the way it tore into big names in the musicological world. Now it seems like a landmark. . . Richard Taruskin raises important questions about how cultural and artistic judgements are made. -- "Literary Review
Keywords: 19th Century (1801-1900); 20th Century (1901-2000); Music history; Nationalism; Musical style; Definition; Hermeneutics; Russia